Environmental and Ecological Effects of Ocean Renewable Energy Development – A Current Synthesis - George W. Boehlert (Oceanography, 2010)
Marine renewable energy promises to assist in the effort to reduce carbon emissions worldwide. As with any large-scale development in the marine environment, however, it comes with uncertainty about potential environmental impacts, most of which have not been adequately evaluated—in part because many of the devices have yet to be deployed and tested. We review the nature of environmental and, more specifically, ecological effects of the development of diverse types of marine renewable energy—covering marine wind, wave, tidal, ocean current, and thermal gradient—and discuss the current state of knowledge or uncertainty on how these effects may be manifested. Many of the projected effects are common with other types of development in the marine environment; for example, additional structures lead to concerns for entanglement, habitat change, and community change. Other effects are relatively unique to marine energy conversion, and specific to the type of energy being harnessed, the individual device type, or the reduction in energy in marine systems. While many potential impacts are unavoidable but measurable, we would argue it is possible (and necessary) to minimize others through careful device development and site selection; the scale of development, however, will lead to cumulative effects that we must understand to avoid environmental impacts. Renewable energy developers, regulators, scientists, engineers, and ocean stakeholders must work together to achieve the common dual objectives of clean renewable energy and a healthy marine environment.